Electrospinning polyethylene terephthalate glycol - Hassan, Mohamed H. (2024)
Polyethylene terephthalate glycol (PETG) is a difficult-to-spin material, and no previous papers have reported the correct conditions to create PETG meshes. To address this issue, a preliminary study on the solubility and electrospinnability of PETG using a range of solvent system was conducted and a Teas graph was established to select the ideal solvent system. Based on these preliminary results, electrospun PETG fibers were produced using a highly volatile binary solvent system consisting of dichloromethane (DCM) and trifluoroacetic acid (TFA). Produced meshes were extensively characterized, and the results demonstrated for the first time the ability of electrospun PETG meshes to support the inoculation and germination of yellow rust spores, thus confirming that PETG is an ideal material to be used for the fabrication of agriculture biosensors. The results also showed that the best solvent split was 85/15 (DCM/TFA).